School counseling: Partnering with a school district to provide postsecondary opportunities for first generation, low income, and students of color - Perusse, Rachelle; Deronck, Nicole G; Parzych, Jennifer (Psychology in the Schools, 2017)
A classroom activity led by district school counselors was conducted in a K-12 school district to ensure educational equity for students in relation to postsecondary attendance. This took place in a school setting that has a large population of students of color, predominately Latino and African American students, as well as low-income students. As part of their practicum field experience, university school counseling students were supervised by school counselors at their sites to help provide a readily available and modified curriculum to instruct students about their options related to postsecondary awareness, planning, and attendance, as well as demonstrate career pathways that engender high expectations and college and career readiness. Instruction took place in the classroom as well as in small group settings.
Keywords: dept.csp; peer-reviewed; postsecondary opportunities